Reflexivity, methodology and contexts in participatory digital media research: making games with Latin American youth in London - Paula, Bruno de (Learning, Media and Technology, 2021)
In this paper, I intend to explore the role played by reflexivity in grounding a more critical perspective when designing, implementing and analysing participatory digital media research. To carry out this methodological reflection, I will present and discuss a recently concluded research project on young people’s game-making in an after-school programme targeting Latin American migrants in London/UK. I will pay special attention to how my subjectivities influenced planning, data generation and analysis of this programme, and to how context, lived experiences, curricular decisions and interpersonal relationships shaped the kinds of knowledge produced through this research. Findings emerging from this experience included relevant dissonances between curricular design/decisions and the use of participatory approaches in game-making, and the limitations of traditional analytical categories within the Social Sciences field (e.g., gender and intersectionality) to understanding subjectivities expressed through game-making. This study offers relevant insights into the place of reflexivity in research on digital media production by young people by highlighting its complexity and by calling for more critical and less homogenising approaches to this type of research.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Recherche-création; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; 5-Créatrice; 5-Identités diasporiques; _Nettoyé

Korean Soap Operas, Telenovelas and Sci-fi Conspiracies: A Game-making Experience with Latin American Youth in London - Paula, Bruno de (Digital Culture and Education, 2021)
This paper explores a game-making programme for 14 Latin American migrants aged 13-18 in London/UK, carried out between October/2017-January/2018, where I investigated the relationships between game conventions, platforms and personal preferences in the curation of fluid identities through game production. Participants presented varying levels of affinity with games linked both to access issues and to other specific elements (e.g. perception of games in contemporary culture, gender). Questionnaires, observations, unstructured/semistructured interviews and gaming archives were employed to explore this participatory initiative and data was analysed through Multimodal Sociosemiotics. Findings remarked how shared understandings about digital games can find their way into platforms and act as “cultural-technical gatekeepers”, supporting or hindering the engagement with game-making of those often perceived as outsiders to gaming culture. This gatekeeping happens when there are “creative dissonances” between, for example, personal preferences and platforms aligned to normative/mainstream genres. These dissonances, however, can end up fostering subversive designs, contravening gaming conventions and potentially challenging traditional gaming boundaries. This insight is relevant for understanding “cultural-technical constraints” and subversive/non-mainstream game-making, especially in relation to innovation and appropriation of game-making resources/strategies by non-mainstream groups.
Keywords: 1-Jeux vidéo; 1-TV; 2-Recherche-création; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; 5-Identités diasporiques; _Nettoyé

Entertaining Africans: Creative Innovation in the (Internet) Television Space - Dovey, Lindiwe (Television in Africa in the Digital Age, 2021)
Despite great heterogeneity, the vast continent of Africa and the diverse people of its countries and diasporas have often been represented through the most reductive, essentialising, and denigrating paradigms— a process that Nigerian writer Chimamanda Adichie Ngozi has referred to as “the danger of a single story”. One of the most dangerous of these paradigms is the developmentalist one, which shoehorns Africa into a western, capitalist teleological framework that overlooks and denies Africa’s production of and participation in forms of leisure, pleasure and entertainment.
Keywords: 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 3-Afrique (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Identités diasporiques; Royaume-Uni (corpus analysé); Royaume-Uni (lieu de production du savoir); _Nettoyé

McTV: Understanding the Global Popularity of Television Formats - Waisbord, Silvio (Television & New Media, 2004)
Globalization has intensified interconnectivity among television industries worldwide. Interconnectivity happens through structural and institutional linkages among television systems and industries worldwide, resulting in an increasingly integrated global business governed by similar practices and goals. The dynamics are reflected in the popularity of television formats. On the surface, global dissemination of formats may suggest not only the global integration of the economy of the industry but also the standardization of content. A dozen media companies are able to do business worldwide by selling the same idea, and audiences seem to be watching national variations of the same show. At a deeper level, however, formats attest to the fact that television still remains tied to local and national cultures. Bringing up examples of Latin American cases, this article argues that television is simultaneously global and national, shaped by the globalization of media economics and the pull of local and national cultures.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; Argentine (corpus analysé); Brésil (corpus analysé); Mexique (corpus analysé); Royaume-Uni (corpus analysé); _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Sexe, Race et Gaming - Derfoufi, Mehdi (Revue du Crieur, 2019)
Aucune étude n’a jamais démontré que les formes médiatiques disposeraient d’un pouvoir direct de transformation des réalités sociales. Une approche critique un peu sérieuse préférera ainsi appréhender le jeu vidéo comme le site d’un ensemble de rapports de pouvoir opérant au sein de la culture dominante, traversé, à l’instar d’autres formes culturelles, par des contradictions, des résistances et des réappropriations – autrement dit par des circulations dans la production de sens, les formes et les affects, qui viennent renforcer, nuancer ou déstabiliser les normes de l’hégémonie culturelle. Depuis le début des années 2010 et en particulier la polémique du #GamerGate en 2014, la communauté vidéoludique ne peut plus ignorer le sexisme. Les féministes n’ont pourtant pas attendu si longtemps pour se manifester. Mais c’est peut-être l’année 2012 qui marqua un réel tournant, lorsque Anita Sarkeesian lança une campagne de crowdfunding pour une série de vidéos sur sa chaîne YouTube feministfrequency. Sa démarche déclencha une vague de cyberharcèlement qui alla des insultes aux menaces de mort et jusqu’à la publication de données personnelles. Ce modèle de violence sexiste s’est reproduit à de multiples reprises, notamment en France en 2013 à l’encontre de la créatrice de jeu et féministe Mar_Lard, attaquée pour sa critique argumentée du sexisme dans la culture geek. Elle revenait en particulier sur des propos plus que complaisants d’un journaliste à propos d’une séquence où le personnage de Lara Croft, héroïne du mythique je…
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; _Nettoyé

Racisme et jeu vidéo - Derfoufi, Mehdi (Éditions de la Maison des sciences de l'homme, 2021)
En 2007, le monde du jeu vidéo est secoué par une violente polémique au sujet du jeu vidéo Resident Evil 5. Ce dernier est accusé de faire commerce du racisme, en invitant à se glisser dans la peau d'un américain blanc body-buildé, missionné dans une région africaine anonyme, et tuant des dizaines d'hommes et de femmes noires présentées comme de dangereux zombies infectés du virus T. Depuis, la communauté des joueurs et joueuses de jeux vidéo interpelle régulièrement les créateurs et créatrices des jeux sur les questions du racisme et du sexisme.Dans son ouvrage, Mehdi Derfoufi analyse les rapports de force qui structurent l'industrie du jeu vidéo, dévoilant comment le racisme se niche parfois insidieusement au cœur de scénarios de jeux vidéo à succès. Il nous invite à nous questionner. Quels sont les pays qui pèsent sur les milliards d'euros du marché mondial du jeu vidéo ? Qui sont les game designers et auteurs des jeux ? Comment les représentations racistes sont-elles véhiculées à travers les personnageset les imaginaires vidéoludiques ? L'auteur nous dévoile avec brio les logiques racialisantes à l’œuvre au sein d’un marché économique très concurrentiel où des stéréotypes exotisants servent régulièrement à faire vendre un jeu. Il nous montre aussi comment la division internationale du travail et la hiérarchie économico-politique Nord/Sud pèse sur le marché du jeu vidéo et ralentit l’émergence de nouvelles représentations. Pourtant, de nombreux espoirs, notamment dans les pays du Sud participent au renouvellement de la culture geek : face aux violences racistes, la riposte s’organise.
Keywords: 1-Jeux vidéo; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; _Nettoyé

L’imbrication classe et sexe à l’œuvre : parcours identitaires et migratoires chez les personnes trans MtF latino-américaines - Gonzalez, Olga L. (Genre, Sexualité & Société, 2018)
Ce travail s’intéresse à la population trans MtF latino-américaine issue des secteurs populaires. Le travail a pour objectifs de (1) connaître les normes de genre du milieu d’origine de cette population (2) comprendre le lien du milieu d’origine avec leur parcours dans l’identité trans (3) examiner les parcours migratoires et comprendre leur très forte inscription dans la prostitution. L’enquête de terrain a été réalisée principalement en France et en Espagne. Concernant le cheminement identitaire, la recherche montre le poids de la formation sociale du milieu d’origine, et particulièrement le poids des normes relatives au genre dans les milieux populaires (hétéronormativité, homophobie, sanction des masculinités déviantes). Cette imbrication classe/sexe situe les personnes dans la position sociale marginale et stigmatisée de la prostitution. L’article apporte un éclairage sur cet environnement, où l’imaginaire festif côtoie l’ordinaire des violences. L’expérience migratoire, très valorisée dans le pays d’origine, est examinée. Le type de liens tissés avec la famille, et les difficultés liées à l’isolement linguistique et à la solitude sont abordés.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 3-Amérique du Sud (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; _Nettoyé

All About Almodóvar’s Men - Rey, Juan; Uceda Pérez, Francisco (Masculinity Studies: Literary and Cultural Representations, 2017)
Pedro Almodóvar is an internationally acclaimed Spanish director. The national and international fascination over Almodóvar's cinema lies in his ability to reflect the problems of contemporary society, his lucidity in combining the urban and the rural, his ability to express the frustrations of modern man, as well as his freshness and spontaneity. Although the vast majority of studies on this Spanish director have focused on women and the gay world, his films are crowded with many types and archetypes of heterosexual men. This groundbreaking edited volume studies the men in the cinema of Almodóvar from a broad yet comprehensive and complementary perspective. Each chapter of All About Almodóvar's Men methodically dissects these male characters—their misery and their greatness, their frustrations and their desires—offering a kaleidoscopic view of man that goes beyond the narrow framework in which many studies have locked the rich cinema of Almodóvar.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Identités diasporiques; _Nettoyé

L'Atlantique noir: modernité et double conscience - Gilroy, Paul (Éditions Amsterdam, 2010)
Qu'est-ce que l'identité noire ? Contre ceux qui en défendent une conception ethniciste ou nationaliste, ou qui cherchent avant tout à en préserver l'authenticité, Paul Gilroy montre comment cette identité complexe, nourrie d'une diversité irréductible, repose sur l'existence d'un espace transnational en constante transformation, qui n'est pas spécifiquement africain, américain, caribéen ou britannique, mais tout cela à la fois : l'Atlantique noir. L'objet de ce livre est de donner à voir l''existence de cet espace constitué dès le XVIIe siècle à travers l'histoire de la traite négrière, de retracer ce réseau serré de relations, d'échanges à multiples sens, d'idées, d'hommes et de productions culturelles. Au fil de pages peuplées par les figures les plus hétéroclites, de Spike Lee à Walter Benjamin en passant par les Jubilee Singers, Richard Wright, W. E. B. Du Bois, Jimi Hendrix, Wynton Marsalis et Hegel, l'espace et le temps singuliers de l'Atlantique noir prennent forme et consistance de façon saisissante. La musique, mode d'expression de prédilection d'une culture enracinée dans l'expérience des terreurs indicibles de l'esclavage, avec ses usages et ses allers-retours inattendus d'un bord à l'autre de l'Atlantique, joue ici un rôle de premier plan. Le retour sur l'esclavage et son caractère intrinsèquement moderne, opéré dans les oeuvres de nombreux écrivains noirs, ouvre par ailleurs à une relecture critique de la modernité, d'une portée universelle, au même titre que la critique des conceptions figées et réductrices de l'identité.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 3-Afrique (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Identités diasporiques; _Nettoyé

Queer/Palestinian Cinema: A Critical Conversation on Palestinian Queer and Women's Filmmaking - Jankovic, Colleen; Nadia, Awad (Camera Obscura: Feminism, Culture, and Media Studies, 2012)
While expanding critiques of pinkwashing have drawn increasing attention to how queer issues in Israel and the Occupied Palestinian Territories are perniciously mobilized by a network of lobby groups, Brand Israel initiatives, and international gay and lesbian organizations, these critiques often fail to consider how queer Palestinians mobilize and understand themselves. This article reports on an October 2011 panel and film screening at Yale University and the Hagop Kevorkian Center for Near Eastern Studies at New York University. “Queer/Palestinian: Critical Strategies in Palestinian Queer and Women's Filmmaking” uniquely focused on questions of queerness and Palestine through a program of eight new Palestinian visual productions. The program brought together Palestinian film scholars, filmmakers, visual artists, and curators for a discussion of queer and feminist artistic practice in relation to Palestinian strategies for resistance. Together, the “Queer/Palestinian” films suggest the urgency for Palestinian visual artists to persistently generate new means of expressing, embodying, and critiquing visions for Palestinian society. Films such as Victoria Moufawad-Paul's Nus Enssas/ صيصنصن (Canada, 2011) and Raafat Hattab's Hourieh (Palestine, 2011) explore issues ranging from queer diasporic solidarity politics and challenges to out/closeted binaries and to the creative reinscription of nakba narratives. Nadia Awad's Two Adaptations of the Same Novel (US, 2011), Suzy Salamy's 1982/2006 (US, 2006), and Moufawad-Paul's Rejoice, O My Heart / يبلق اي حرفا (Canada, 2011) suggest an irreverent queer strategy by undermining the narrative conventions and visual codes of mainstream news media and popular US and Egyptian cinema. Salamy's video, previously projected through mobile exhibition on city buildings, and Eli Rezik's online “web-movies” Living Alone without Me (Palestine, 2011) and Between Us Two (Palestine, 2011) compelled a panel discussion of alternative means of distribution and exhibition. Finally, Alaa AbuAsad's Masturbate bil beit (Palestine, 2011) rounded out the program with an explicitly erotic and unapologetically political version of the meeting of “queer” and “Palestinian.”
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Europe (corpus analysé); 5-Identités diasporiques; _Nettoyé